Analysis of P670 Pump Machine Effectiveness through OEE and TPM Methods at PT. XYZ - Mohammad Ridho Nurfadi; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2025)
PT. XYZ is a cooking oil manufacturing company. The machine used in the processing is the P670 pump machine, which causes a decline in the CPO process, resulting in an increase in the defect rate. This study was conducted to evaluate machine performance and defect factors using the OEE and TPM methods. The OEE analysis showed a value of 84%, which is below the international standard of 85%, and identified Six Big Losses with the highest percentage being Idling & Minor Stoppages Losses at 43.80%. In addition, five factors were identified, namely man, method, machine, material, and environment. Based on these results, improvements were made, namely cleaning schedules, adding alarm control sensors, machine maintenance, and operator training. To ensure effective implementation, a special team of technicians and operators was formed to oversee the implementation of improvements, evaluate by comparing OEE values before and after, conduct training every 2 weeks or once a month, assign a work area coordinator, develop a structured maintenance schedule, and establish a routine cleaning duty roster. Companies must apply these results to reduce losses in terms of time, product defects, effectiveness, and machine performance.